2016
DOI: 10.4244/eijy15m07_04
|View full text |Cite
|
Sign up to set email alerts
|

High-sensitivity C-reactive protein predicts 10-year cardiovascular outcome after percutaneous coronary intervention

Abstract: In patients undergoing PCI, higher CRP levels at the time of the procedure are predictive for 10-year mortality and myocardial infarction. High-sensitivity CRP may be a useful biomarker to improve further risk assessment in patients undergoing PCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 27 publications
0
14
0
3
Order By: Relevance
“…Показана связь между вероятностью рестеноза и содержанием в крови пациентов различных воспалительных маркеров (вч-СРБ, моноцитарный хемотаксический белок-1, миелопероксидаза, кардиотропин-1, интерлейкин-6, показатели активности тромбоцитов) [28][29][30][31]. Согласно результатам исследований [32][33][34], повышенный уровень вч-СРБ в пред-, пери-и в постпроцедурном периодах является фактором риска рестеноза в стенте. Согласно данным мета-анализа 6 проспективных исследований, включивших 1156 пациентов с ИБС (всего имплантировано 885 стентов, рестеноз внутри стента зарегистрирован в 194 случаях), высокие уровни вч-СРБ ассоциировались с повышенным риском рестеноза в стенте в течение 6-12 мес и определяли худший прогноз пациентов данной категории после коронарного стентирования [35].…”
Section: Discussionunclassified
“…Показана связь между вероятностью рестеноза и содержанием в крови пациентов различных воспалительных маркеров (вч-СРБ, моноцитарный хемотаксический белок-1, миелопероксидаза, кардиотропин-1, интерлейкин-6, показатели активности тромбоцитов) [28][29][30][31]. Согласно результатам исследований [32][33][34], повышенный уровень вч-СРБ в пред-, пери-и в постпроцедурном периодах является фактором риска рестеноза в стенте. Согласно данным мета-анализа 6 проспективных исследований, включивших 1156 пациентов с ИБС (всего имплантировано 885 стентов, рестеноз внутри стента зарегистрирован в 194 случаях), высокие уровни вч-СРБ ассоциировались с повышенным риском рестеноза в стенте в течение 6-12 мес и определяли худший прогноз пациентов данной категории после коронарного стентирования [35].…”
Section: Discussionunclassified
“…There is compelling evidence for an association between the elevated hsCRP and the long-term (follow-up of 4.8 years) risk of acute CV events such as CV death, MI, or stroke in patients with stable CHD [28]. Preprocedural hsCRP predicts long-term (up to 10-year follow-up) CV outcomes such as mortality, MI, stroke, and stent thrombosis in patients with stable CHD undergoing PCI with coronary artery stenting [29,32].…”
Section: Crp For CV Risk Assessmentmentioning
confidence: 99%
“…Rapidly accumulating evidence demonstrated the important role of CRP concentration for clinical risk stratification in patients with ACS with regard to mortality, recurrent MI, in-stent restenosis, and composite clinical endpoints [20,21,29,31,32,[35][36][37][38][39][40][41][42][43][44]. A meta-analysis by He et al [36] indicated that higher early CRP concentration (within the first 72 h of ACS onset) increases long-term risk of recurrent CV events (including MI) or death, and may be a valuable prognostic predictor after ACS, including homogenous populations with MI.…”
Section: Crp For Prediction Of Adverse Outcomes In Acsmentioning
confidence: 99%
“…High-sensitivity C-reactive protein (hsCRP), a sensitive serum marker of acute and chronic systemic inflammation [1,2], is closely associated with outcomes of patients with various types of coronary heart diseases (CHD), including stable CHD and myocardial infarction (MI), and those undergoing percutaneous coronary intervention (PCI) [3][4][5][6]. Therefore, inflammation was generally considered detrimental in the context of atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%